Pengaruh Pertumbuhan Ekonomi, Pendapatan Asli Daerah, Dana Alokasi Umum, Dana Alokasi Khusus Dan Sisa Lebih Pembiayaan Anggaran Terhadap Belanja Modal Kabupaten/Kota Di Provinsi Jawa Tengah Periode 2013-2014 - Apriyanto, Jati Dwi; , Drs. Wahyono, Ak, MA (2016)
Implementation of fiscal decentralization in improving services and needs in various sectors of the public sector one, giving authority to local governments to provide capital expenditure for the development of higher beneficial sectors in each region. The purpose of this research is to obtain empirical evidences of the influence of Economic Growth, Local Own Revenue (PAD), General Purpose Grant (DAU), Special Purpose Grant (DAK), and Surplus of budget financing altogether in allocating capital expenditure in districts/cities in central java province. In this study, the sampling method used was saturated sampling technique, where the entire population to be sampled. Population in this study is all local governments In central java Province for year of 2013 - 2014. In java central Province, there are 35 local governments which consist of 29 districts and 6 cities. The data used is Budget Realisation Statements of districts/cities in central java Province which had been audited by BPK. The test results showed PAD, DAK, and SiLPA positive and significant impact on capital expenditures in the Districts / Cities in central java Province, while economic growth and DAU have not significant effect on capital expenditurein the Districts / Cities in central java Province